(NHC)NiH‐Catalyzed Regiodivergent Cross‐Hydroalkenylation of Vinyl Ethers with α‐Olefins: Syntheses of 1, 2‐ and 1, 3‐Disubstituted Allyl Ethers. (9th February 2018) - Chen, Weihao; Li, Yang; Chen, Yang; Ho, Chun‐Yu
Abstract: Cross‐hydroalkenylation of a vinyl ether (1 ) with an α‐olefin (2 ) was first achieved by a set of [NHC‐Ni(allyl)]BAr F (NHC=N‐heterocyclic carbene) catalysts. Both 1, 2‐ and 1, 3‐disubstituted allyl ethers were obtained, highly selectively, by using NHCs of different sizes. In contrast, the chemoselectivity (i.e., 1 as acceptor and2 as donor) was controlled mostly by electronic effects through the catalyst–substrate interaction. Sterically bulkier alkenes (2 ) were used as preferred donors compared to smaller alkenes. This electronic effect also served as a basis for the first tail‐to‐head cross‐hydroalkenylations of1 with either a vinyl silane or boronic ester.